A Prospective Clinical and Ultrasounic Assessment of Urinary Litholytic Activity of Cynodon Dactylon Aqueous Extract - Karrar Kamoona; Fadhid Abdul Jabbar; Hussein Abdul Kadhim; Sahar A. Majeed (Kufa Journal for Nursing Sciences)
Background: Urolithiasis is one of the common health problems which endanger renal function due to ureteral obstruction and hydro nephrosis.